REGULATION OF BANKS OF UKRAINE AS THE DOMINANT FINANCIAL MARKET PARTICIPANTS - Kovalenko , V.V. (The actual problems of regional economy development, 2016)
The article aims to study methods and instruments for regulating banks in Ukraine. Proved that the stable activities of banks Ukraine to some extent dependent on the efficient functioning of the regulation. Compared to all the participants of the financial market, banks occupy a dominant niche in it from a position of financial services and their role in the rise of economic growth in the country. The article is to develop recommendations for improving regulation of banks Ukraine in terms of balancing the regulatory impact on all financial intermediaries and the subsequent introduction of macroprudential regulation. It is proved that further improve the system of regulation of banks Ukraine is based on the implementation of the strategy macroprudential regulation and supervision and implementation in Ukraine model based on “twin peaks”. Substantiated that the regulation of banks Ukraine is the foundation to ensure their financial sustainability, which will contribute to economic recovery in the state. JEL: G 28